Cobweb-shaped nano-array self-supporting electrode, preparation method thereof and application thereof in alkaline electrolyzed water and anion exchange membrane electrolyzed water
By using spiderweb-like nanoarray self-supporting electrodes in alkaline water electrolysis and anion exchange membrane water electrolysis, the problems of slow electrode reaction kinetics and stability were solved, achieving low overpotential and high stability electrocatalytic effects, which are suitable for long-term stable operation of industrial electrolyzers.
Patent Information
- Application Number
- CN202511616120.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-06
- Publication Date
- 2026-01-16
AI Technical Summary
In existing alkaline water electrolysis and anion exchange membrane water electrolysis hydrogen production technologies, the electrode reaction kinetics are slow, the overpotential of the oxygen evolution reaction at the anode is high, and the electrodes are easily corroded and detached in alkaline solutions, resulting in a decrease in catalyst activity and failing to meet the requirements for stable industrial operation.
A spiderweb-like nanoarray self-supporting electrode is adopted, including a nickel-based metal self-supporting layer and a bimetallic nanosheet array active layer. Spiderweb-like LDH nanosheets are formed by in-situ growth of bimetallic nanosheets and iron ion exchange method, which improves the physical structural stability and specific surface area of the catalyst and enhances the active sites.
It achieves lower overpotential and excellent electrode stability, improves electrocatalytic activity and reaction kinetics, and meets the requirements of low energy consumption and long-term stable operation of industrial electrolyzers.
Smart Images

Figure CN121344660A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of alkaline and anion exchange membrane electrolysis for hydrogen production, and in particular to a spider web-like nanoarray self-supporting electrode, its preparation method, and its application in alkaline and anion exchange membrane electrolysis. Background Technology
[0002] Hydrogen energy is considered one of the most promising future energy carriers due to its high energy density and the fact that its combustion product is only water. Electrolysis of water to produce hydrogen, which uses electricity generated from renewable energy sources (such as solar and wind power) to decompose water into high-purity hydrogen and oxygen, is a key pathway to achieving large-scale production of "green hydrogen" and has significant strategic importance for building a low-carbon energy system.
[0003] However, current water electrolysis technologies, especially high-efficiency alkaline water electrolysis and the emerging alkaline anion exchange membrane water electrolysis for hydrogen production, still face many challenges for large-scale commercial application. One of the core bottlenecks lies in the slow electrode reaction kinetics, particularly the oxygen evolution reaction at the anode, which requires a highly active electrocatalyst to reduce the overpotential of the reaction, thereby improving energy conversion efficiency and reducing energy consumption. Another core bottleneck is that the electrodes are prone to metal dissolution and large-area detachment under alkaline solutions and scouring. On the one hand, the dissolved metal ions redeposit on the surface of the membrane / ion exchange membrane, causing membrane pore blockage, increased resistance, and further amplifying system polarization. On the other hand, continuous bubble peeling promotes crack propagation, causing the catalyst layer to peel off in whole pieces in a "scale-like" or "cluster-like" manner, exposing a low-activity or inert metal substrate. After detachment, the current density in the exposed area increases locally, exacerbating the further corrosion of the substrate by the alkaline solution, forming a vicious cycle of "dissolution-detachment-redissolution". This ultimately leads to a sharp decline in electrode activity, while the interface resistance increases and the mass transfer channels become blocked, causing the cell voltage to rise by tens of millivolts every hundred hours, which fails to meet the long-term stable operation requirements of industrial electrolytic cells. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides a spiderweb-like nanoarray self-supporting electrode, its preparation method, and its application in alkaline water electrolysis and anion exchange membrane water electrolysis. The self-supporting electrode for alkaline water electrolysis prepared by this invention exhibits low overpotential and excellent stability, solving two major bottleneck problems in anode catalysts and simultaneously achieving a win-win situation in terms of activity and stability. This lays a solid foundation for expanding the electrode from laboratory research to practical industrial applications.
[0005] The first objective of this invention is to provide a spiderweb-like nanoarray self-supporting electrode, comprising a substrate, and a bimetallic nanosheet array active layer and a spiderweb-like LDH nanosheet active layer sequentially disposed on the surface of the substrate; furthermore, the active layer is disposed on at least one side of the substrate, which can be either both sides or one side.
[0006] The substrate is a nickel-based metal self-supporting layer; The active layer of the bimetallic nanosheet array is NiCoLDH nanosheets; The spiderweb-like LDH nanosheet active layer comprises NiFeLDH and NiCoLDH nanosheets.
[0007] In some test examples of the present invention, the substrate is loose and porous, the active layer is tightly bonded to the substrate, and the active layer is a rough porous spider web-like nanoarray.
[0008] The substrate includes nickel foam, nickel felt, and nickel-iron foam.
[0009] In some test examples of the present invention, the thickness of the substrate is 0.1-0.5 μm; the thickness of the spider web-like LDH nanosheet active layer is 0.1-1 μm; and the size of the NiFeLDH and NiCoLDH nanosheets is 3-10 μm.
[0010] The second objective of this invention is to provide a method for fabricating the aforementioned spiderweb-like nanoarray self-supporting electrode, comprising the following steps: A pretreated substrate is provided, as well as a metal salt solution containing nickel salt and cobalt salt; The organic ligand is added to the metal salt solution to obtain the precursor solution; The substrate is placed in the precursor solution at room temperature, and a bimetallic nanosheet array active layer is grown in situ on the surface of the substrate to form a precursor template. Iron salts are dissolved in an aqueous solution, and then an organic solvent is added. After mixing, an iron ion hydrolysis solution is obtained. The precursor template is placed in the iron ion hydrolysis solution for a water bath reaction to form a spider web-like LDH nanosheet active layer, thus obtaining the spider web-like nanoarray self-supporting electrode.
[0011] In some test examples of the present invention, the substrate is subjected to degreasing and surface oxide layer treatment. The treatment process includes sequentially acid treatment, water washing, alcohol washing, and vacuum drying of the substrate. The acid used for acid treatment is hydrochloric acid with a concentration of 4-5 wt%, and the alcohol used for alcohol washing is anhydrous ethanol with a purity of ≥99.5%.
[0012] In some test examples of the present invention, the nickel salt is selected from one or more of nickel nitrate hexahydrate, nickel sulfate, nickel chloride, or nickel acetate, and the concentration of the nickel salt in the metal salt solution is 0.025~0.4 mol / L. Exemplarily, it can be 0.025 mol / L, 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, etc., or any range between any two values. The cobalt salt is selected from one or more of cobalt nitrate hexahydrate, cobalt acetate, or cobalt chloride; the concentration of the cobalt salt in the metal salt solution is 0.025-0.1 mol / L, and for example, it can be 0.025 mol / L, 0.05 mol / L, 0.075 mol / L, 0.1 mol / L, or any range between any two values; The molar ratio of the nickel salt and the cobalt source is (1:1) to (4:1). For example, it can be 1:1, 2:1, 3:1, 4:1, or any range between any two values.
[0013] Furthermore, after the smooth, leaf-shaped NiCoLDH nanoarray (in-situ grown bimetallic nanosheet array active layer) is generated, it is rinsed multiple times with deionized water and ethanol and then placed in a vacuum drying oven for drying.
[0014] In some test examples of the present invention, the in-situ growth conditions were: 20~35 °C, and a standing time of not less than 4 hours. Further, a standing time of 4 hours was preferred.
[0015] In some test examples of the present invention, the iron salt is selected from one or more of ferric chloride, ferric nitrate nonahydrate, or ferric sulfate; In some test examples of the present invention, the concentration of the iron salt is 0.02-1 mol / L. Exemplarily, it can be 0.02 mol / L, 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, or any range between any two values. In some test examples of this invention, the conditions for the water bath reaction were: a water bath reaction temperature of 50-100°C and a reaction time of 0.5-24 h. In the water bath reaction described in this invention, both displacement reaction and coprecipitation reaction occurred simultaneously.
[0016] Furthermore, after the spiderweb-like NiFeLDH / NiCoLDH nanosheet array is grown in the active layer of the spiderweb-like LDH nanosheets, it is rinsed multiple times with deionized water and ethanol in sequence and then dried in a vacuum drying oven to obtain the finished electrode.
[0017] A third objective of the present invention is to provide an apparatus for alkaline water electrolysis (ALK-WE) and anion exchange membrane water electrolysis (AEM-WE), comprising the aforementioned spider web nanoarray self-supporting electrode.
[0018] The technical solution of the present invention has the following advantages compared with the prior art: 1. A smooth, leaf-shaped NiCoLDH nanoarray is formed as a precursor using a simple in-situ growth method. The precursor is tightly bonded to the nickel substrate, which helps to achieve a more uniform stress distribution and better interfacial adhesion, thereby improving the physical structure stability of the catalyst. It also provides a larger specific surface area and more active sites to enhance catalytic activity.
[0019] 2. Co atoms in the NiCoLDH nanosheet precursor are partially replaced by iron ion exchange to form the NiFeLDH / NiCoLDH catalyst active layer. The NiFeLDH / NiCoLDH layer exhibits a unique spider web-like nanosheet array with abundant pore structure and active sites, which greatly increases the specific surface area of the catalyst and enhances its mass transfer capacity.
[0020] 3. In both ALK-WE and AEM-WE processes, NiFeLDH / NiCoLDH exhibits faster reaction kinetics than NiFeLDH or NiCoLDH alone, and demonstrates lower overpotential and superior current stability in simulated electrolytic cells. This can be attributed to the fact that the NiFeLDH / NiCoLDH active layer anchors the nickel substrate through chemical bonding, improving the physical structural stability of the electrode and reducing the dissolution and loss of active components. Simultaneously, the synergistic effect among the NiFeCo trimetallic compounds facilitates precise control of the electronic structure of the active centers, constructing high-density active sites and enhancing electrode chemical stability, achieving a win-win situation for both activity and stability. This approach holds promise for meeting the requirements of low-energy consumption and long-term stable operation of industrial electrolytic cells. Attached Figure Description
[0021] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific test examples and accompanying drawings, wherein... Figure 1 These are SEM images of some comparative examples and test cases of the present invention; wherein, (a) comparative example 1, (b) comparative example 2, and (c) test case 1.
[0022] Figure 2SEM images of some test examples of the present invention; wherein, (a) test example 1, (b) test example 2, (c) test example 3, and (d) test example 4.
[0023] Figure 3 These are XRD patterns of the comparative examples and test example 1 of this invention.
[0024] Figure 4 These are (a) LSV curves, (b) overpotentials, (c) Tafel curves, and (d) C values of the comparative examples and test example 1 of this invention. dl Curves, (e)ECSA, (f)TOF.
[0025] Figure 5 This is an LSV curve of the comparative example and test example 1 (ac) at different temperatures.
[0026] Figure 6 The following are the LSV curves, overpotentials, Tafel curves, and C values of Comparative Example 1 and some test examples of this invention: (a) LSV curves, (b) overpotentials, (c) Tafel curves, and (d) C values. dl Curves, (e)ECSA, (f)TOF.
[0027] Figure 7 These are (a) Nyquist plots and (b)-(d) Bode plots of the comparative examples and test example 1 of this invention.
[0028] Figure 8 This is (a) DRT diagram of test example 1 of the present invention.
[0029] Figure 9 The following are current density-voltage relationship curves of test examples and comparative examples of the present invention: (a) AEM-WE, (b) runtime-voltage relationship curve of test example 5, (c) ALK-WE, and (d) runtime-voltage relationship curve of test example 6. Detailed Implementation
[0030] The present invention will be further described below with reference to the accompanying drawings and specific test examples, so that those skilled in the art can better understand and implement the present invention. However, the test examples are not intended to limit the present invention.
[0031] The test example of the spiderweb-like nanoarray self-supporting electrode of the present invention includes nickel foam, a NiCoLDH nanosheet precursor grown on the nickel foam, and a spiderweb-like NiFeLDH / NiCoLDH nanosheet active layer obtained by ion exchange of the NiCoLDH precursor. The NiCoLDH nanosheet precursor is tightly bonded to the nickel foam substrate. Through strong chemical bonds formed by metal-oxygen-metal covalent bonds and the mechanical interlocking effect generated by the three-dimensional porous structure of the nickel substrate, it provides structural support and stress buffer for the catalyst, increasing the physical structural stability of the catalyst. At the same time, the nanosheet array provides a large specific surface area for the catalyst, increasing the number of active sites and improving the mass transfer of the catalyst. In addition, the synergistic effect of the NiFeCo trimetallic layer is conducive to the precise control of the electronic structure of the active center, constructing a high-density active site and improving the chemical stability of the electrode. The NiFeLDH / NiCoLDH catalytic active layer and the nickel substrate form an electron transfer pathway through tight interfacial contact. Electrons generated by the active layer can be rapidly transferred to the nickel foam substrate, synergistically improving the overall catalytic activity.
[0032] Specifically, the ALK-WE and AEM-WE electrodes prepared in this application are described in detail with the following comparative examples and test cases.
[0033] Comparative Example 1: This comparative example provides a method for fabricating a self-supporting electrode by in-situ growth of NiCoLDH nanosheet arrays on nickel foam, including the following steps: (1) Cut commercial 0.3 mm thick nickel foam into 2 cm*2 cm pieces, place them in 4 wt% hydrochloric acid and sonicate for 30 min, then rinse with deionized water until neutral, sonicate with deionized water for 10 min, then replace with clean deionized water and sonicate for 20 min, and finally sonicate with anhydrous ethanol for 30 min. Place them in a vacuum drying oven at 60 ℃ and dry for 12 h for later use.
[0034] (2) Dissolve 1 mmol of Ni(NO3)2·6H2O and 1 mmol of Co(NO3)2·6H2O in 40 mL of deionized water and stir for 10 min to form solution A. Dissolve 15 mmol of dimethylimidazole in 40 mL of deionized water and stir for 10 min to form solution B.
[0035] (3) Pour solution A into solution B and mix and stir for 1 min to obtain a mixed solution. Quickly immerse the 2 cm*2 cm nickel foam that has been pretreated in step (1) into the mixed solution. After standing at room temperature for 4 h, take out the nickel foam and rinse it with deionized water. Then rinse the nickel foam with anhydrous ethanol and put it into a vacuum drying oven. Dry it at 60 ℃ for 12 h to obtain the self-supporting electrode of the in-situ grown NiCoLDH nanosheet array.
[0036] Comparative Example 2: This comparative example provides a method for preparing NiFeLDH self-supporting electrodes via a one-step water bath method on nickel foam, including the following steps: (1) Cut commercial 0.3 mm thick nickel foam into 2 cm*2 cm pieces, place them in 4 wt% hydrochloric acid and sonicate for 30 min, then rinse with deionized water until neutral, sonicate with deionized water for 10 min, then replace with clean deionized water and sonicate for 20 min, and finally sonicate with anhydrous ethanol for 30 min. Place them in a vacuum drying oven and dry at 60 ℃ for 12 h for later use.
[0037] (2) Dissolve 3 mmol of FeCl2·4H2O in 8 mL of deionized water and stir for 10 min to obtain solution A. Then pour the obtained solution A into 42 mL of anhydrous ethanol to obtain an iron ion solution.
[0038] (3) Immerse the 2 cm*2 cm nickel foam pretreated in step (1) into the iron ion solution obtained in step (2) and place it in a constant temperature heating magnetic stirrer. React at 50 °C for 6 h. After the reaction, remove the nickel foam and rinse it with deionized water. Then rinse the nickel foam with anhydrous ethanol and place it in a vacuum drying oven. Dry it at 60 °C for 12 h to obtain the NiFeLDH self-supporting electrode.
[0039] Comparative Example 3: Comparative Example 1 was cut into 2 cm * 2 cm pieces and used as the anode. A commercial platinum-carbon electrode was selected as the cathode, and a commercial composite diaphragm Agfa220 was selected as the diaphragm. The electrode was assembled in an electrolytic cell fixture, and the electrolyte was a 30 wt% KOH solution. The voltage of the electrolytic cell fixture was tested at different current densities at 80 °C.
[0040] Comparative Example 4: Comparative Example 2 was cut into 2 cm * 2 cm pieces and used as the anode. A commercial platinum-carbon electrode was selected as the cathode, and a commercial composite diaphragm Agfa220 was selected as the diaphragm. The electrodes were assembled in an electrolytic cell fixture, and the electrolyte was a 30 wt% KOH solution. The voltage of the electrolytic cell fixture was tested at different current densities at 80 °C.
[0041] Comparative Example 5: A piece of Comparative Example 1 was cut into 1 cm * 1 cm pieces and used as the anode. A commercial platinum-carbon electrode was selected as the cathode, and a commercial anion exchange membrane was selected as the diaphragm. The electrode was assembled in an electrolytic cell fixture. The electrolyte was a 1 M KOH solution. The voltage of the electrolytic cell fixture was tested at different current densities at 60 °C.
[0042] Comparative Example 6: A piece of Comparative Example 2 was cut into 1cm*1cm pieces and used as the anode. A commercial platinum-carbon electrode was selected as the cathode, and a commercial anion exchange membrane was selected as the diaphragm. The electrode was assembled in an electrolytic cell fixture. The electrolyte was a 1M KOH solution. The voltage of the electrolytic cell fixture was tested at different current densities at 60 °C.
[0043] Test Example 1: This test example provides a method for fabricating a spiderweb-like nanoarray self-supporting electrode, as detailed below: (1) Cut commercial 0.3 mm thick nickel foam into 2 cm*2 cm pieces, place them in 4 wt% hydrochloric acid and sonicate for 30 min, then rinse with deionized water until neutral, sonicate with deionized water for 10 min, then replace with clean deionized water and sonicate for 20 min, and finally sonicate with anhydrous ethanol for 30 min. Place them in a vacuum drying oven and dry at 60 ℃ for 12 h for later use.
[0044] (2) Dissolve 1 mmol of Ni(NO3)2·6H2O and 1 mmol of Co(NO3)2·6H2O in 40 mL of deionized water and stir for 10 min to form solution A. Dissolve 15 mmol of dimethylimidazole in 40 mL of deionized water and stir for 10 min to form solution B.
[0045] (3) Pour solution A into solution B and mix for 1 min to obtain a mixed solution. Quickly immerse the 2 cm*2 cm nickel foam that has been pretreated in step (1) into the mixed solution. After standing at room temperature for 4 h, take out the nickel foam and rinse it with deionized water. Then rinse the nickel foam with anhydrous ethanol and put it into a vacuum drying oven. Dry it at 60 ℃ for 12 h to obtain nickel foam with in-situ grown NiCoLDH nanosheet array.
[0046] (4) Dissolve 3 mmol of FeCl2·4H2O in 8 mL of deionized water and stir for 10 min to obtain solution C. Then pour the obtained solution C into 42 mL of anhydrous ethanol to obtain Fe ion solution.
[0047] (5) The nickel foam obtained in step (3) is immersed in the Fe ion solution obtained in step (4) and placed in a constant temperature heating magnetic stirrer. The reaction is carried out at 50 °C for 6 h. After the reaction is completed, the nickel foam is taken out and rinsed with deionized water, then rinsed with anhydrous ethanol. The nickel foam is placed in a vacuum drying oven and dried at 60 °C for 12 h to obtain a high-efficiency oxygen evolution spider web-like NiFeLDH / NiCoLDH nanoarray self-supporting electrode (NiFeLDH / NiCoLDH-6h).
[0048] Test Example 2: This test example provides a method for fabricating a spiderweb-like nanoarray self-supporting electrode, as detailed below: (1) Cut commercial 0.3 mm thick nickel foam into 2 cm*2 cm pieces, place them in 4 wt% hydrochloric acid and sonicate for 30 min, then rinse with deionized water until neutral, sonicate with deionized water for 10 min, then replace with clean deionized water and sonicate for 20 min, and finally sonicate with anhydrous ethanol for 30 min. Place them in a vacuum drying oven and dry at 60 ℃ for 12 h for later use.
[0049] (2) Dissolve 1 mmol of Ni(NO3)2·6H2O and 1 mmol of Co(NO3)2·6H2O in 40 mL of deionized water and stir for 10 min to form solution A. Dissolve 15 mmol of dimethylimidazole in 40 mL of deionized water and stir for 10 min to form solution B.
[0050] (3) Pour solution A into solution B and mix for 1 min to obtain a mixed solution. Quickly immerse the 2 cm*2 cm nickel foam that has been pretreated in step (1) into the mixed solution. After standing at room temperature for 4 h, take out the nickel foam and rinse it with deionized water. Then rinse the nickel foam with anhydrous ethanol and put it into a vacuum drying oven. Dry it at 60 ℃ for 12 h to obtain nickel foam with in-situ grown NiCoLDH nanosheet array.
[0051] (4) Dissolve 3 mmol of FeCl2·4H2O in 8 mL of deionized water and stir for 10 min to obtain solution C. Then pour the obtained solution C into 42 mL of anhydrous ethanol to obtain Fe ion solution.
[0052] (5) The nickel foam obtained in step (3) is immersed in the Fe ion solution obtained in step (4) and placed in a constant temperature heating magnetic stirrer. The reaction is carried out at 50 °C for 2 h. After the reaction is completed, the nickel foam is taken out and rinsed with deionized water, then rinsed with anhydrous ethanol. The nickel foam is placed in a vacuum drying oven and dried at 60 °C for 12 h to obtain a high-efficiency oxygen evolution spider web-like NiFeLDH / NiCoLDH nanoarray self-supporting electrode (NiFeLDH / NiCoLDH-2h).
[0053] Test Example 3: This test example provides a method for fabricating a spiderweb-like nanoarray self-supporting electrode, as detailed below: (1) Cut commercial 0.3 mm thick nickel foam into 2 cm*2 cm pieces, place them in 4 wt% hydrochloric acid and sonicate for 30 min, then rinse with deionized water until neutral, sonicate with deionized water for 10 min, then replace with clean deionized water and sonicate for 20 min, and finally sonicate with anhydrous ethanol for 30 min. Place them in a vacuum drying oven and dry at 60 ℃ for 12 h for later use.
[0054] (2) Dissolve 1 mmol of Ni(NO3)2·6H2O and 1 mmol of Co(NO3)2·6H2O in 40 mL of deionized water and stir for 10 min to form solution A. Dissolve 15 mmol of dimethylimidazole in 40 mL of deionized water and stir for 10 min to form solution B.
[0055] (3) Pour solution A into solution B and mix for 1 min to obtain a mixed solution. Quickly immerse the 2 cm*2 cm nickel foam that has been pretreated in step (1) into the mixed solution. After standing at room temperature for 4 h, take out the nickel foam and rinse it with deionized water. Then rinse the nickel foam with anhydrous ethanol and put it into a vacuum drying oven. Dry it at 60 ℃ for 12 h to obtain nickel foam with in-situ grown NiCoLDH nanosheet array.
[0056] (4) Dissolve 3 mmol of FeCl2·4H2O in 8 mL of deionized water and stir for 10 min to obtain solution C. Then pour the obtained solution C into 42 mL of anhydrous ethanol to obtain Fe ion solution.
[0057] (5) The nickel foam obtained in step (3) is immersed in the Fe ion solution obtained in step (4) and placed in a constant temperature heating magnetic stirrer. The reaction is carried out at 50 °C for 4 h. After the reaction is completed, the nickel foam is taken out and rinsed with deionized water, then rinsed with anhydrous ethanol. The nickel foam is placed in a vacuum drying oven and dried at 60 °C for 12 h to obtain a high-efficiency oxygen evolution spider web-like NiFeLDH / NiCoLDH nanoarray self-supporting electrode (NiFeLDH / NiCoLDH-4h).
[0058] Test Example 4: This test example provides a method for fabricating a spiderweb-like nanoarray self-supporting electrode, as detailed below: (1) Cut commercial 0.3 mm thick nickel foam into 2 cm*2 cm pieces, place them in 4 wt% hydrochloric acid and sonicate for 30 min, then rinse with deionized water until neutral, sonicate with deionized water for 10 min, then replace with clean deionized water and sonicate for 20 min, and finally sonicate with anhydrous ethanol for 30 min. Place them in a vacuum drying oven and dry at 60 ℃ for 12 h for later use.
[0059] (2) Dissolve 1 mmol of Ni(NO3)2·6H2O and 1 mmol of Co(NO3)2·6H2O in 40 mL of deionized water and stir for 10 min to form solution A. Dissolve 15 mmol of dimethylimidazole in 40 mL of deionized water and stir for 10 min to form solution B.
[0060] (3) Pour solution A into solution B and mix for 1 min to obtain a mixed solution. Quickly immerse the 2 cm*2 cm nickel foam that has been pretreated in step (1) into the mixed solution. After standing at room temperature for 4 h, take out the nickel foam and rinse it with deionized water. Then rinse the nickel foam with anhydrous ethanol and put it into a vacuum drying oven. Dry it at 60 ℃ for 12 h to obtain nickel foam with in-situ grown NiCoLDH nanosheet array.
[0061] (4) Dissolve 3 mmol of FeCl2·4H2O in 8 mL of deionized water and stir for 10 min to obtain solution C. Then pour the obtained solution C into 42 mL of anhydrous ethanol to obtain Fe ion solution.
[0062] (5) The nickel foam obtained in step (3) is immersed in the Fe ion solution obtained in step (4) and placed in a constant temperature heating magnetic stirrer. The reaction is carried out at 50 °C for 8 h. After the reaction is completed, the nickel foam is taken out and rinsed with deionized water, then rinsed with anhydrous ethanol. The nickel foam is placed in a vacuum drying oven and dried at 60 °C for 12 h to obtain a high-efficiency oxygen evolution spider web-like NiFeLDH / NiCoLDH nanoarray self-supporting electrode (NiFeLDH / LDH-8).
[0063] Test Example 5: A piece of Test Example 1 was cut into 1 cm * 1 cm pieces and used as the anode. A commercial platinum-carbon electrode was selected as the cathode, and a commercial anion exchange membrane was selected as the diaphragm. The electrode was assembled in an electrolytic cell fixture. The electrolyte was a 1 M KOH solution. The voltage of the electrolytic cell fixture was tested at different current densities at 60 °C.
[0064] Test Example 6: Test Example 1 was cut into 2 cm * 2 cm pieces and used as the anode. A commercial platinum-carbon electrode was selected as the cathode, and a commercial composite diaphragm Agfa220 was selected as the diaphragm. The diaphragm was assembled in an electrolytic cell fixture. The electrolyte was a 30 wt% KOH solution. The voltage of the electrolytic cell fixture was tested at different current densities at 80 °C.
[0065] To clearly observe the structural morphology of the synthesized electrodes and their formation process, SEM characterization was used to analyze the morphology of the NiCoLDH nanosheet precursor electrode grown on nickel foam, the NiFeLDH electrode obtained by iron ion etching of nickel foam, and the final spiderweb-like NiFeLDH / NiCoLDH electrode. Figure 1 The images shown in Figures 1 and 2 are SEM images of the Ni-based self-supporting electrodes prepared in Comparative Example 1, Comparative Example 2, and Test Example 1, respectively. Figure 1 As can be seen in Figure a, in Comparative Example 1, the (NiCoLDH) electrode is formed by in-situ growth of smooth, leaf-like nanosheets on nickel foam, creating a uniform and dense nanoarray; as shown in Figure a. Figure 1 As shown in Figure b, the (NiFeLDH) electrode in Comparative Example 2 exhibits a large number of white particles and clustered structures of varying sizes; Figure 1 As shown in Figure c, the electrode (NiFeLDH / NiCoLDH) obtained in Test Example 1 can be clearly seen. The spider web-like nanoskeleton composed of nanosheet arrays can be clearly seen, indicating that after iron ion exchange, NiCoLDH is partially etched into NiFeLDH / NiCoLDH, and the surface of the nanosheets becomes rough, exhibiting a typical LDH morphology. Figure 2 The images in 'ad' are SEM images of test samples with different ion exchange times, representing the Ni-based self-supporting electrodes prepared for Test Example 1, Test Example 2, Test Example 3, and Test Example 4, respectively. Figure 2 As can be seen in Figure a, Test Example 1 has a relatively dense porous structure with relatively uniform pores. The particles are stacked to form a spider web-like morphology, and the surface is relatively regular. Figure 2 As shown in Figure b, the surface of Test Example 2 exhibits a porous mesh structure, with a relatively loose LDH sheet structure, obvious cracks, and unevenly distributed particle aggregation; as shown in Figure b. Figure 2 As shown in Figure c, LDH sheets agglomerate into blocky structures with relatively compact structures and rough surfaces, and the LDH sheet structure gradually becomes blurred; as Figure 2 As shown in Figure d, a large number of fine particles aggregate into a loose, clustered structure with numerous pores and cracks. This indicates that the morphology of NiFeLDH / NiCoLDH is gradually destroyed with increasing ion exchange time, and the surface LDH nanosheet array is covered by clustered particles. To better understand the evolution of the crystal structure during electrode synthesis, XRD characterization was used for further analysis. Figure 3As shown, in Test Example 1, the (111), (200), and (220) crystal planes of nickel foam, as well as multiple crystal planes of NiFeLDH / NiCoLDH, can be observed simultaneously. For comparison, Comparative Examples 1 and 2 also perfectly match the standard cards. It is noteworthy that although the standard peak positions of NiFeLDH and NiCoLDH are basically overlapping, the LDH peak position in Test Example 1 is negatively shifted compared to Comparative Examples 1 and 2. This is due to the interaction between NiFeLDH and NiCoLDH. The peak of the nickel foam substrate also shows a certain shift in the three electrodes, which is due to the synergistic effect between NiFeCo metals. Compared to Comparative Example 2, the LDH peak intensity in Test Example 1 is stronger, indicating better crystallinity and demonstrating that NiCoLDH is more conducive to the growth of NiFeLDH on the self-supporting layer. However, compared to Comparative Example 1, the LDH peak intensity is weaker, indicating that the introduction of Fe reduces the crystallinity of the material, causing lattice distortion and certain defects, which is consistent with the SEM results.
[0066] For alkaline oxygen evolution (OER) performance testing and impedance (EIS) testing, electrocatalytic oxygen evolution tests were conducted in a standard three-electrode system using 1.0 MKOH as the electrolyte to study the influence of electrode structure and multi-metal synergy on OER performance. The working electrode was the electrode prepared in Comparative Examples 1-2 and Test Examples 1-4, the counter electrode was a graphite rod, and the reference electrode was a Hg / HgO electrode. It was placed in a 1 mol / L KOH electrolyte at room temperature (25 ℃). Cyclic voltammetry (CV) activation was performed using a Chenhua electrochemical workstation. The working electrode was activated at 50 mV s⁻¹ within a voltage range of -1.6 to 1.1 V vs. RHE. -1 The scan rate was cycled 30 times for activation. All linear sweep voltammetry (LSV) tests were performed over a voltage range of 0–1.1 V vs. RHE. EIS tests were performed from 100 kHz to 0.01 Hz. In-situ impedance Bode plots were obtained over a voltage range of 0–0.55 V vs. RHE.
[0067] LSV curve as follows Figure 4 As shown in Figure a, it can be seen that Test Example 1 achieves the highest current density, requiring only an overpotential of 243 mV to reach 1000 A / m. -2 The current density is much lower than the overpotential required for Comparative Example 1 (382 mV) and Comparative Example 2 (305 mV). Figure 4 (b) Besides overpotential, which indicates the catalytic performance of an electrode, the Tafel slope is also used to characterize the reaction kinetics in the OER process; a smaller Tafel slope indicates faster reaction kinetics. The Tafel slopes for Test Example 1, Comparative Example 1, and Comparative Example 2 are 67, 79.3, and 108.9 mV dec, respectively.-1 ( Figure 4 As shown in c), this indicates that Test Example 1 exhibits superior reaction kinetics, demonstrating that a stable nanoarray structure and bimetallic synergistic effect can simultaneously optimize OER reaction kinetics. Since the geometric area affects the catalytic activity of the material during electrode fabrication, the dual capacitance (Cd) was obtained by linear fitting through measurements of CV at different scan rates in the non-Radidatic interval. dl )like Figure 4 As shown in d, the calculation results show that C for Comparative Example 1, Comparative Example 2, and Test Example 1 dl The values were 5.7, 10.9, and 11.9 mF / cm. -2 Using C dl Further conversion of these values yields the electrochemically active surface area (ECSA) of each material, such as... Figure 4 As shown in Figure e, Test Example 1 exhibits the largest ECSA, indicating that it possesses more catalytic active sites. Furthermore, the turnover frequency (TOF) based on the number of active sites can be used to evaluate the activity per active site. The TOF values for Test Example 1, Comparative Example 1, and Comparative Example 2 are 0.15, 0.02, and 0.06 s, respectively. -1 ( Figure 4 (f) It can be seen that the turnover frequency of Test Example 1 is much higher than that of other materials, indicating that it has optimal intrinsic activity. The excellent catalytic activity exhibited by Test Example 1 can be attributed to the synergistic effect of the three metals promoting reaction kinetics, and the spiderweb-like nanoframework providing a larger specific surface area and more active sites, thereby improving OER performance. The apparent activation energy of the test examples and comparative examples was evaluated by kinetic analysis as a function of temperature to assess the catalytic stability of the materials at different temperatures. Figure 5 Figure (ac) shows the polarization curves of Test Example 1, Comparative Example 1, and Comparative Example 2 at different temperatures. It can be seen that the overpotential of the samples increases with increasing temperature, but Test Example 1 and Comparative Example 2 are less sensitive to temperature, indicating that the introduction of NiFeLDH can give the electrode better catalytic stability.
[0068] To investigate the effect of iron ion content on catalyst performance, an experimental time gradient from 0 h to 8 h was set up. Electrocatalytic oxygen evolution tests were conducted using 1.0 M KOH as the electrolyte in a standard three-electrode system. Figure 6 The LSV display shows that at 1000 A m -2At the specified current density, the overpotentials of Test Example 1, Test Example 2, Test Example 3, Test Example 4, and Comparative Example 1 were 243 mV, 276 mV, 269 mV, 251 mV, and 401 mV, respectively. The overpotential showed a trend of first decreasing and then increasing with increasing iron ion content, reaching its minimum at a replacement time of 6 h. This indicates that the catalyst exhibits optimal activity at this time. However, when the iron ion concentration further increases, the overpotential begins to rise. This is because excessively high iron ion concentration leads to the agglomeration of metal particles, thereby reducing the active sites of the catalyst, and larger agglomerated particles are prone to causing the catalyst layer to detach during water electrolysis. Figure 6 As shown in c, the Tafel slopes of Comparative Example 1, Test Example 2, Test Example 3, Test Example 4, and Test Example 1 are 105.7, 77.9, 76.0, 74.2, and 67.0 mV dec, respectively. -1 The Tafel slope also showed a trend of first decreasing and then increasing with the increase of iron ions, reaching its minimum at a replacement time of 6 h. This further proves that Test Example 1 has faster reaction kinetics, indicating that the amount of Fe introduced at this time is optimal, and the synergistic effect of NiFeLDH and NiCoLDH reaches the optimal balance, which can maximize the promotion of OER reaction kinetics and enhance electrocatalytic activity. Figure 6 As shown in d, the calculation results show that C is the same for Comparative Example 1, Test Example 2, Test Example 3, Test Example 4, and Test Example 1. dl The values were 2.6, 6.7, 9.4, 11.9, and 10.8 mF / cm. -2 The chart shows a volcano pattern with an initial increase followed by a decrease. Using C... dl Further conversion of the value yields the ECSA for each material, such as Figure 6 As shown in Figure e, Test Example 1 exhibits the highest ECSA, exceeding that of Test Examples 2, 3, 4, and Comparative Example 1. This indicates that Test Example 1 achieves the optimal iron ion concentration, possesses a greater number of catalytically active sites, and exhibits higher intrinsic catalytic activity, which is beneficial for operation under high current densities. Figure 6 The calculations shown in f yielded TOF values of 0.027, 0.02, 0.016, 0.148, and 0.15 s for each electrode at an overpotential of 250 mV. -1 We can see that the turnover frequency of Test Example 1 is much higher than that of other materials, indicating that it has the best intrinsic catalytic activity. The reason for the high turnover frequency of Test Example 1 is that the effect of iron ion doping reaches an optimal balance, which can endow it with a high specific surface area, maximize the exposure of active sites while ensuring the number of effective active sites, and balance the synergistic effect of the three metals, thereby enhancing the reaction kinetics and improving the OER performance.
[0069] Electrode stability is crucial in practical applications, and the electron transfer rate in electrocatalysis significantly impacts performance. Electrochemical impedance spectroscopy (EIR) can be used to further investigate the OER kinetics of different catalysts. Figure 7 The Nyquist plot of a was obtained under the condition of 0.606 V vs. RHE. All points obtained from the test are based on the equivalent circuit diagram ( Figure 7 (As shown in the inset a) can be fitted into three parts, including the electrolyte impedance R s and charge transfer impedance R ct =R ct1 +R ct2 (Specific values are shown in Table 3). The charge transfer impedance was lowest in Test Example 1 at 0.44 Ω, compared to 2.15 Ω in Comparative Example 1 and 0.51 Ω in Comparative Example 2. This indicates rapid electron transfer in both NiFeLDH and NiFeLDH / NiCoLDH electrodes, demonstrating good mass transfer capacity and conductivity. However, electron transfer was slower in the NiCoLDH electrode. This is because Co material has poor intrinsic conductivity; the introduction of Fe ions partially converts it to NiFeLDH, improving its conductivity. Since the electrocatalytic oxygen evolution process is usually accompanied by catalyst reconstruction, the speed of catalyst reconstruction also affects OER performance. To further investigate the influence of the synergistic effect of nanosheet arrays and bimetals on the composite material properties and the interfacial interaction process, the Bode plots of the synthesized catalysts were analyzed in detail. Figure 7 As shown in Figure bd, Bode plots obtained from in-situ EIS testing of all electrodes show that, in the range of 0.924-1.474 V, the phase angle of electrode 1 in the high-frequency region begins to decrease, indicating surface oxidation reconstruction, during which no significant current is generated. When the potential reaches 1.274 V, oxidation is complete, and the phase angle shifts from the high-frequency region to the low-frequency region, signifying the start of the OER process, at which point the current begins to increase significantly. Furthermore, as the potential increases, the phase angle in the low-frequency region gradually decreases, indicating the onset of a vigorous OER process. Similarly, in Comparative Example 1 and Comparative Example 2 electrodes, the potentials at which surface oxidation reconstruction is completed are 1.399 V and 1.374 V, respectively, indicating a slower oxidation process, thus increasing the OER onset potential. Analysis of the results further demonstrates a synergistic effect between the NiFeLDH and NiCoLDH activation layers, which can promote electrode surface reconstruction, improve reaction kinetics, and reduce the OER onset potential. To further analyze the impedance changes during the OER process, we analyzed the interfacial electrochemical processes in different frequency regions using time relaxation curves (DRT). Figure 8 The diagram shown is the relaxation time plot of Test Example 1. It can be observed that the four peaks correspond to the ion diffusion resistance (Z). w Hydrogen evolution and oxygen evolution charge transfer resistance (R)ct1 and R ct2 ) and water vapor mass transfer resistance (R s R ct The peak intensity decreases continuously with increasing voltage and shifts towards the lower frequency region, indicating that rapid charge transfer has occurred. Furthermore, the peak value of NiFeLDH / NiCoLDH hardly decreases after the voltage reaches 1.324 V, indicating that the water electrolysis reaction has been completed at this point, which is consistent with the trend shown in the Bode plot.
[0070] Regarding the electrolytic cell testing, one group used composite electrodes from Test Example 1 (NiFeLDH / NiCoLDH), Comparative Example 1 (NiCoLDH), and Comparative Example 2 (NiFeLDH) cut into 1 cm x 1 cm pieces as anodes, and commercial platinum-carbon electrodes as cathodes; commercial anion exchange membranes were used as diaphragms. These were assembled into an electrolytic cell testing apparatus, with a 1 M KOH solution as the electrolyte and a temperature of 60 °C. The voltage of the electrolytic cell apparatus was measured at different current densities. Another group used composite electrodes from Test Example 1, Comparative Example 1, and Comparative Example 2 cut into 2 cm x 2 cm pieces as anodes, and commercial platinum-carbon electrodes as cathodes; commercial composite diaphragms were used as diaphragms. These were assembled into an electrolytic cell testing apparatus, with a 30 wt% KOH solution as the electrolyte and a temperature of 80 °C. The voltage of the electrolytic cell apparatus was measured at different current densities. Figure 9 As shown in Figure a, at 3000 A / m 2 At the specified current density, the assembled electrolytic cell voltages for Test Example 5, Comparative Example 5, and Comparative Example 6 were 1.631 V, 1.661 V, and 1.832 V, respectively; at an electrolytic cell voltage of 2 V, the current densities for Test Example 5, Comparative Example 5, and Comparative Example 6 reached 15031 A / m. 2 8301 A / m 2 and 13837 A / m 2 For stability testing, a 1 cm x 1 cm NiFeLDH / NiCoLDH electrode was used as the anode, a commercial platinum-carbon electrode as the cathode, and a commercial anion exchange membrane as the diaphragm. This was assembled into an electrolytic cell testing apparatus. The electrolyte was a 1 M KOH solution, the temperature was 60 °C, and the test was conducted at 5000 A / m². 2 The electrolytic cell was operated at the current density for 120 hours, and the voltage of the electrolytic cell was recorded, such as... Figure 9 As shown in Figure b, the voltage of Test Example 5 remained basically stable over 120 h, indicating that the NiFeLDH / NiCoLDH electrode still possesses a certain degree of AEM stability under industrial current density. Figure 9 As shown in c, at 10000 A / m 2At the specified current density, the assembled electrolytic cell voltages for Test Example 6, Comparative Example 3, and Comparative Example 4 were 1.72 V, 1.88 V, and 1.8 V, respectively; at an electrolytic cell voltage of 2 V, the current densities for Test Example 6, Comparative Example 3, and Comparative Example 4 reached 20846 A / m. 2 14478 A / m 2 and 18149 A / m 2 For stability testing, a 2 cm x 2 cm NiFeLDH-NF electrode was used as the anode, and a commercial platinum-carbon electrode was selected. A commercial composite diaphragm was used. The device was assembled in an electrolytic cell testing apparatus. The electrolyte was a 30 wt% KOH solution, and the temperature was 80 ℃. The voltage of the electrolytic cell was measured at different current densities. Figure 9 As shown in Figure d, the voltage retention rate of Test Example 6 reached 91.2% after 275 h, indicating that the NiFeLDH / NiCoLDH electrode exhibits excellent ALK stability at industrial current densities. In summary, the spiderweb-like nanoframework and the synergistic effect of the three metals in this invention optimize the catalytic activity of both ALK-WE and AEM-WE. Furthermore, this invention can simultaneously improve the catalytic activity and structural stability of the electrode under operating conditions, providing a feasible strategy for designing low-energy-consumption, ultra-durable bifunctional nickel-based self-supporting electrodes.
[0071] Table 1. Resistance values (R0) calculated from electrochemical impedance spectroscopy of the comparative examples and test examples of this invention. s Electrolyte resistance; R ct (charge transfer resistance) Material <![CDATA[R ct (ohm)]]> <![CDATA[R s (ohm)]]> Test Example 1 0.44 1.127 Comparative Example 1 2.15 1.262 Comparative Example 2 0.51 1.129 Table 2. Oxygen evolution performance of the comparative examples and test examples of the present invention. Material <![CDATA[Current density (A m -2 )]]> Overpotential (mV) <![CDATA[Current density (A m -2 )]]> Voltage <![CDATA[Current density (A m -2 )]]> Voltage Test Example 1 100 243 / / / / Test Example 2 100 276 / / / / Test Example 3 100 269 / / / / Test Example 4 100 251 / / / / Comparative Example 1 100 382 / / / / Comparative Example 2 100 305 / / / / Comparative Example 3 / / 10000 1.88 14478 2 Comparative Example 4 / / 10000 1.8 18149 2 Comparative Example 5 / / 3000 1.832 8307 2 Comparative Example 6 / / 3000 1.661 13837 2 Test Example 5 / / 3000 1.631 15031 2 Test Example 6 / / 10000 1.72 20846 2 Obviously, the test examples above are merely illustrative and not intended to limit the implementation. Those skilled in the art will recognize that various variations and modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations. However, any obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A spider-webbed nanoarray self-supporting electrode, characterized in that, The substrate, and a bimetallic nanosheet array active layer and a spiderweb-like LDH nanosheet active layer arranged on the surface of the substrate in sequence; The substrate is a nickel-based metal self-supporting layer; The bimetallic nanosheet array active layer is a NiCoLDH nanosheet; The spiderweb-like LDH nanosheet active layer comprises NiFeLDH and NiCoLDH nanosheets.
2. The spider-web nanometer array free-standing electrode of claim 1, wherein, The substrate is loose and porous; The substrate comprises a foamed nickel, a nickel felt, or a foamed nickel-iron.
3. The spider-web nanometer array free-standing electrode of claim 1, wherein, The thickness of the spiderweb-like LDH nanosheet active layer is 0.1-1 μm, and the size of the NiFeLDH and NiCoLDH nanosheets is 3-10 μm.
4. A method of producing a self-supporting electrode of a spider-web nanomesh according to any one of claims 1 to 3, characterized in that, The method comprises the following steps: A pretreated substrate and a metal salt solution containing a nickel salt and a cobalt salt are provided; An organic ligand is added to the metal salt solution to obtain a precursor solution; The substrate is placed in the precursor solution to in-situ grow a bimetallic nanosheet array active layer on the surface of the substrate, forming a precursor template; An iron salt is dissolved in an aqueous solution and then an organic solvent is added, and after mixing, an iron ion hydrolysis solution is obtained; The precursor template is placed in the iron ion hydrolysis solution for water bath reaction to form a spiderweb-like LDH nanosheet active layer, thereby obtaining the spiderweb-like nanosheet array self-supporting electrode.
5. The preparation method according to claim 4, characterized in that, The nickel salt is selected from one or more of nickel nitrate hexahydrate, nickel sulfate, nickel chloride, or nickel acetate, and the concentration of the nickel salt in the metal salt solution is 0.025-0.4 mol / L; The cobalt salt is selected from one or more of cobalt nitrate hexahydrate, cobalt acetate, or cobalt chloride, and the concentration of the cobalt salt in the metal salt solution is 0.025-0.1 mol / L; The molar ratio of the nickel salt to the cobalt salt is (1:1)-(4:1).
6. The preparation method according to claim 4, characterized in that, The in-situ growth conditions are 20-35 ℃ and the static time is not less than 4 hours; The organic ligand is selected from one or more of imidazole, benzimidazole, or 2-methylimidazole; The molar ratio of the metal salt to the organic ligand is (1:8)-(1:32).
7. The preparation method according to claim 4, characterized in that, The iron salt is selected from one or more of ferric chloride, ferric nitrate nonahydrate, or ferric sulfate; The organic solvent is selected from one or more of methanol, ethanol, or isopropanol.
8. The preparation method according to claim 4, characterized in that, The concentration of the iron salt is 0.02-1 mol / L.
9. The preparation method according to claim 4, characterized in that, The water bath reaction conditions are a water bath reaction temperature of 50-100 ℃ and a reaction time of 0.5-24 h.
10. An apparatus for electrolysis of water by alkaline electrolysis or by anion exchange membrane electrolysis, characterized in that, The spiderweb-like nanosheet array self-supporting electrode of any one of claims 1-3.